Comparison of Government and Private Based Waqf Institutions Management: Case Study of Indonesia And Malaysia - Raditya Sukmana; Anwar Allah Pitchay; Mohamad Isa Abd Jalil (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2021)
The present study aims to compare two (2) different types of management, i.e., privatization and nationalization, in managing waqf assets development. We compared the experiences of two (2) countries; firstly, Malaysia, which is controlled by the government-based institution, and secondly, Indonesia, which is governed by the private based institution. Therefore, this issue has prompted the purpose of this study; first (1st) to investigate and compare waqf assets development in both countries; second (2nd) to explore issues faced by both countries in developing waqf assets and third (3rd) solutions for the future direction of waqf practice in both countries. To achieve this objective, we employed two different methods which are library research and field research. Library research data comprised of secondary data where information is extracted from waqf institutions’ annual reports and websites, relevant books, journals, internet websites and scientific conference papers were utilised. Meanwhile, field research involves information gathered from expert interviews. In the context of Malaysia, we interviewed eight (8) respondents which comprised of four (4) waqf institution officers, three (3) academic researchers and one (1) Bank officer who offers cash waqf product. Meanwhile, in the context of Indonesia, we interviewed four (4) waqf institution officers. The data are analysed based on the inductive approach. Based on the experts’ interviews, we identify three (3) major themes and eight (8) subthemes that explained the condition of the waqf management in both countries. We find that waqf institutions in both countries faced similar issues in management such as lack of expertise in economic and finance employed in waqf institution, lack of standardization in financial reports and also lack of capital to develop the waqf assets. Besides management issues, we find that Muslims in both countries have low literacy levels about waqf due to confusion and lack of practice of waqf in society and to improve this situation, the waqf institutions in both countries are educating the Muslims on the importance of waqf through various programmers. Moreover, we discover that the younger generation in Malaysia could not contribute waqf in the form of fixed assets due to the scarcity of land and the high value of land and building, especially in urban areas. The final theme relates to the solution for both countries in developing waqf assets. We find that experts from both countries recommended the promotion of waqf in the form of cash. This is the ideal solution in the present day to not only rejuvenate waqf assets development but also motivate the younger generation to contribute cash waqf. Besides this, the experts are also concerned about the stringent law imposed on waqf assets development. Thus, the experts suggested flexibility in the law, especially to the use of the istibdal (exchange) method to develop waqf lands. The analysis of the study is derived based on qualitative research, and the respondents participating in the study are limited to experts in the field of waqf. Thus, future research in this area may include analysis of interviews related to waqf practice from the perspectives of ordinary Muslims and also distributing the questionnaire to a bigger sample of the population to gauge wider opinion about waqf in both countries. This paper provides an opportunity for further empirical studies to prove that the development of waqf has a significant influence based on the management structure. Furthermore, the outcome of this research provides positive implications for the policymakers from both countries in overcoming problems and also rejuvenating the role of waqf development in their respective countries. This study gauge the two (2) different environment of waqf assets management from two (2) different countries in managing waqf properties using approaches of management.